Circularly Polarized S Band Dual Frequency Square Patch Antenna Using Glass Microfiber Reinforced PTFE Composite. (22nd May 2014) - Samsuzzaman, M.; Islam, M. T.; Arshad, Haslina; Mandeep, J. S.; Misran, N.
Abstract : Circularly polarized (CP) dual frequency cross-shaped slotted patch antenna on 1.575 mm thick glass microfiber reinforced polytetrafluoroethylene (PTFE) composite material substrate is designed and fabricated for satellite applications. Asymmetric cross-shaped slots are embedded in the middle of the square patch for CP radiation and four hexagonal slots are etched on the four sides of the square patch for desired dual frequency. Different substrate materials have been analysed to achieve the desired operating band. The experimental results show that the impedance bandwidth is approximately 30 MHz (2.16 GHz to 2.19 GHz) for lower band and 40 MHz (3.29 GHz to 3.33 GHz) for higher band with an average peak gain of 6.59 dBiC and 5.52 dBiC, respectively. Several optimizations are performed to obtain the values of the antenna physical parameters. Moreover, the proposed antenna possesses compactness, light weight, simplicity, low cost, and circularly polarized. It is an attractive candidate for dual band satellite antennas where lower band can be used for uplink and upper band can be used for downlink.